Optimising the performance and interpretation of small bowel capsule endoscopy - Beg, Sabina; Parra-Blanco, Adolfo; Ragunath, Krish (BMJ Publishing Group, 2017)
Small bowel capsule endoscopy has become a commonly used tool in the investigation of gastrointestinal symptoms and is now widely available in clinical practice. In contrast to conventional endoscopy, there is a lack of clear consensus on when competency is achieved or the way in which capsule endoscopy should be performed in order to maintain quality and clinical accuracy. Here we explore the evidence on the key factors that influence the quality of small bowel capsule endoscopy services.